2016
DOI: 10.1161/atvbaha.115.306944
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Family History, a Genetic Risk Score, and Severity of Coronary Artery Disease in Patients With Premature Acute Coronary Syndromes

Abstract: Objective-A genetic risk score (GRS) for coronary artery disease has recently been shown to be independent of family history (FHx) in predicting future cardiovascular events. We sought to determine whether the presence of these risk factors, either individually or together, was associated with a higher burden of angiographic coronary artery disease. Approach and Results-We included 763 patients with premature acute coronary syndrome (median age, 50 [46-53] years; 30.8% women) with at least 1 major epicardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 46 publications
3
23
1
1
Order By: Relevance
“…(43) Due to lack of data, we could not confirm whether the effect of genetic profiling on fracture risk is dependent on parental history variable. However, studies in the field of cardiovascular disease have suggested that the effect of genetic profiling on coronary heart disease (44,45) is independent of family history.…”
Section: Discussionmentioning
confidence: 99%
“…(43) Due to lack of data, we could not confirm whether the effect of genetic profiling on fracture risk is dependent on parental history variable. However, studies in the field of cardiovascular disease have suggested that the effect of genetic profiling on coronary heart disease (44,45) is independent of family history.…”
Section: Discussionmentioning
confidence: 99%
“…As performed previously [15], we defined multivessel stenosis as having at least two lesions, each with ≥ 50% stenosis, influencing at least two of the four major coronary arteries (left main coronary artery, right coronary artery, left circumflex artery and left anterior descending artery). Each stenotic lesion was graded by a board-certified cardiologist who had additional training in angiography.…”
Section: Definition Of Atherosclerotic Burden In the Mccd Cohortmentioning
confidence: 99%
“…In this study, it was also shown that the CAD is more severe among patients with a positive family history of heart disease than among patients without a positive family history. [31] Other studies on 349 individuals who had referred for angiography were researched by Sunman et al . Patients with a positive family history of heart disease suffered from a higher severity of CAD.…”
Section: Discussionmentioning
confidence: 99%